Exploration of ‘Make in India’: A Lift to Indian Economy - Dr. Manoj Kumar Trivedi (JOURNAL OF MANAGEMENT, SCIENCES, OPERATION & STRATEGIES, 2023)
India is one of the fastest growing economies in the world. But the economy is mostly service driven and the service sector is contributing almost 60% to the country’s GDP. To strengthen the financial power of the nation government of India has emphasized on manufacturing, which will open the door for investment. The Government launched the “Make in India” initiative. Key thrust of the program was that the initiative will make India a manufacturing hub and will eliminating the unnecessary laws and regulations, making bureaucratic processes easier, and ultimately will add to the country’s economy. The study undertaken is qualitative in nature. The purpose of the study is to explore the growth dynamics and the opportunities for manufacturing sector with the light of government’s initiative “Make in India”. Keywords: Make in India, Manufacturing Sector, GDP, Indian Economy